2018
DOI: 10.1002/jcp.27101
|View full text |Cite
|
Sign up to set email alerts
|

Action mechanisms of n‐3 polyunsaturated fatty acids on the oocyte maturation and developmental competence: Potential advantages and disadvantages

Abstract: Infertility is a growing problem worldwide. Currently, in vitro fertilization (IVF) is widely performed to treat infertility. However, a high percentage of IVF cycles fails, due to the poor developmental potential of the retrieved oocyte to generate viable embryos. Fatty acid content of the follicular microenvironment can affect oocyte maturation and the subsequent developmental competence. Saturated and monounsaturated fatty acids are mainly used by follicle components as primary energy sources whereas polyun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 115 publications
0
21
0
1
Order By: Relevance
“…Dietary concentrations of omega-3 fatty acids were shown to determine their deposition in the female reproductive system (follicular fluid, granulosa cells, cumulusoocyte complex, and ovarian tissues) in cattle, ewes, mice, and rats, but the biological significance of these findings remains controversial (70) . It has been suggested that the enhancement of ovulation and fertility promoted by omega-3 polyunsaturated fatty acids might be due to a shift in the biosynthesis of PGE 2 toward the production of less active PGE 3 , thereby preventing the anti-ovulatory effects of excessive PGE 2 (70) . In the current study, a higher intake of DHA was accompanied by increased deposition of this fatty acid in the reproductive tissue of both females and males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary concentrations of omega-3 fatty acids were shown to determine their deposition in the female reproductive system (follicular fluid, granulosa cells, cumulusoocyte complex, and ovarian tissues) in cattle, ewes, mice, and rats, but the biological significance of these findings remains controversial (70) . It has been suggested that the enhancement of ovulation and fertility promoted by omega-3 polyunsaturated fatty acids might be due to a shift in the biosynthesis of PGE 2 toward the production of less active PGE 3 , thereby preventing the anti-ovulatory effects of excessive PGE 2 (70) . In the current study, a higher intake of DHA was accompanied by increased deposition of this fatty acid in the reproductive tissue of both females and males.…”
Section: Discussionmentioning
confidence: 99%
“…Van Niel & Beynen (69) found strong correlations between the intake of LA (R 0•99), ALA (R 0•99), EPA (R 0•94) and DHA (R 0•91) and their deposition in cutaneous adipose tissue in cats. Dietary concentrations of n-3 fatty acids were shown to determine their deposition in the female reproductive system (follicular fluid, granulosa cells, cumulus-oocyte complex and ovarian tissues) in cattle, ewes, mice and rats, but the biological significance of these findings remains controversial (70) . It has been suggested that the enhancement of ovulation and fertility promoted by n-3 PUFA might be due to a shift in the biosynthesis of PGE 2 towards the production of less active PGE 3 , thereby preventing the anti-ovulatory effects of excessive PGE 2 (70) .…”
Section: Discussionmentioning
confidence: 99%
“…4 The follicular levels of n-3 PUFAs are correlated with plasma lipids, which are modified according to diet and body weight. 4 It is hypothesized that n-3 PUFAs can regulate oocyte maturation by mechanisms mediated by functional changes in granulosa cells linked to peroxisome-proliferator-activated receptors (PPARs) and modifications in the biosynthesis of follicular prostaglandins. 4 According to experimental data, PUFAs are potent PPAR ligands and also increase the expression of the steroidogenic acute regulatory protein (STAR).…”
Section: Before Conceptionmentioning
confidence: 99%
“…3 Among the factors related to oocyte quality, maternal diet is highlighted, since obesity and diabetes can alter mitochondrial function and chromosome alignment at the gamete level. 4 Accordingly, the concentration of fatty acids in the ovarian follicular microenvironment is associated with oocyte quality and embryonic development during in vitro fertilization procedures. 4 The follicular levels of n-3 PUFAs are correlated with plasma lipids, which are modified according to diet and body weight.…”
Section: Before Conceptionmentioning
confidence: 99%
“…Por serem componentes da membrana celular, os lipídios podem exercer efeitos vantajosos ou desvantajosos de acordo com as fontes ingeridas, alterando o desenvolvimento embrionário, por exemplo, pela modificação da composição dos AG da bicamada lipídica plasmática dos oócitos (ZAREZADEH et al, 2018).…”
Section: Metabolismo De Lipídeosunclassified